Validação do immunoblot para detecção do h. pylori e avaliação da resposta humoral à infecção em uma comunidade urbana de Fortaleza - Oliveira, Francisco Josemar Alves de (2012)
Infection by H. pylori is presented as one of the most prevalent infections in the world, infecting nearly half the world population, and is directly related to the major gastric disorder. It is known that infection is acquired in infancy and have long duration course. The Immunoblotting is an enzyme immunoassay, noninvasive, which shows itself as an important tool to study the humoral immune response against pathogens, including H. pylori. This technique is very important in epidemiological studies. The aim of this study was to validate the Immunoblotting technique for detection of antibodies against the antigens of H. pylori, using the gold standard with 13C-urea breath test (13C-UBT) and PCR. And to evaluate the profile of the humoral immune response in individuals living in the community University Park. The antigens were extracted and purified from strains isolated from gastric biopsies of dyspeptic patients. The immunoblotting was validated with sera from 46 individuals who had previously conducted 13C-UBT and PCR for genes ureA, vacA and cagA. The sensitivity was 100.0%, specificity 83.3%, Positive Predictive Value 97.6%, Negative Predictive Value of 100%, Positive Likelihood ratio: 6.00, negative Likelihood ratio: 0.00. After the validated method was verified immunoreactivity to H. pylori in 108 patients, which found a prevalence of 87.0%. This population showed a 78.7% positive for VacA protein and 33.3% for CagA. The Immunoblotting was shown to be an excellent technique to identify active or previous infection of H. pylori, due to its high sensitivity and specificity. Seropositivity was high for VacA and the CagA was moderate, thus revealing the expression profile of these cytotoxins by strains circulating in the population studied. Keywords: H.pylori; Immunoblot; VacA and CagA protein.